2020
DOI: 10.1101/2020.08.20.258897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circulating adiponectin mediates the association between omentin gene polymorphism and cardiometabolic health in Asian Indians

Abstract: Background : Plasma omentin levels have been shown to be associated with circulating adiponectin concentrations and cardiometabolic disease-related outcomes. However, the findings have been inconsistent due to high level of confounding. In this study, we aim to examine the association of omentin gene polymorphism with plasma adiponectin levels and cardiometabolic health status using a genetic approach, which is less prone to confounding, and investigate whether these associations are modified by lifestyle fac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Several studies have shown that healthy lifestyle may modify the association between genetic risk and metabolic disease-related traits (10)(11)(12)(13)(14)(15)(16) . Although some studies have shown that increased physical activity levels and healthy diet can attenuate the effect of genetic variants on metabolic traits, other studies have shown conflicting results (17) , which could be attributed to genetic heterogeneity and differences in the dietary patterns across multiple ethnic groups (7,18,19) .…”
mentioning
confidence: 99%
“…Several studies have shown that healthy lifestyle may modify the association between genetic risk and metabolic disease-related traits (10)(11)(12)(13)(14)(15)(16) . Although some studies have shown that increased physical activity levels and healthy diet can attenuate the effect of genetic variants on metabolic traits, other studies have shown conflicting results (17) , which could be attributed to genetic heterogeneity and differences in the dietary patterns across multiple ethnic groups (7,18,19) .…”
mentioning
confidence: 99%